Summation of reciprocals related to z-th power of gf-sequence - Xi, Gaowen (Utilitas Mathematica, 2018)
By applying the method of generating function, we give several summations of reciprocals related to /-th power of GF-Sequence WJ . The purpose of this paper is to give some generalizations for the reciprocal sums of /-th power of generalized Fibonacci sequence Wn. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.